2006
DOI: 10.1037/0278-6133.25.4.521
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of a population- and transtheoretical model-based stress-management intervention.

Abstract: Stress has been associated with a variety of chronic and acute conditions and with higher use of health care services. This research reports on 18-month outcomes of a randomized clinical trial of a stress-management program based on the transtheoretical model (TTM; J. O. Prochaska & C. C. DiClemente, 1986). A national sample of 1,085 individuals participated (age range = 18-91 years, M = 55.33; 68.9% female, 31.1% male; 84.8% Caucasian; 15.2% non-Caucasian). Both the treatment and control groups received asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
117
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(127 citation statements)
references
References 25 publications
7
117
0
2
Order By: Relevance
“…In the national population trial funded by NIH, there was a true no treatment control group that showed only 40% progressing to effective stress management at six months. Further, the outcomes for both the TTM tailoring and control groups were maintained at 12 and 18 months follow-up (Evers et al, 2006).…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…In the national population trial funded by NIH, there was a true no treatment control group that showed only 40% progressing to effective stress management at six months. Further, the outcomes for both the TTM tailoring and control groups were maintained at 12 and 18 months follow-up (Evers et al, 2006).…”
Section: Discussionmentioning
confidence: 92%
“…In the national population trial funded by NIH, there was a true no treatment control group that showed only 40% progressing to effective stress management at six months. Further, the outcomes for both the TTM tailoring and control groups were maintained at 12 and 18 months follow-up (Evers et al, 2006).In this Oregon Worksite Wellness study, the TTM Tailoring (73.9%) and the MI Coaching (78.2%) had even greater efficacy than before (Evers et al, 2006). These results are important in their own right given the effects of stress on personal well-being, health, health care utilization and productivity.…”
mentioning
confidence: 85%
See 3 more Smart Citations